Catalysis‐Driven Self‐Thermophoresis of Janus Plasmonic Nanomotors. Issue 2 (6th December 2016) - Qin, Weiwei; Peng, Tianhuan; Gao, Yanjing; Wang, Fei; Hu, Xiaocai; Wang, Kun; Shi, Jiye; Li, Di; Ren, Jicun; Fan, Chunhai
Abstract: It is highly demanding to design active nanomotors that can move in response to specific signals with controllable rate and direction. A catalysis‐driven nanomotor was constructed by designing catalytically and plasmonically active Janus gold nanoparticles (Au NPs), which generate an asymmetric temperature gradient of local solvent surrounding NPs in catalytic reactions. The self‐thermophoresis behavior of the Janus nanomotor is monitored from its inherent plasmonic response. The diffusion coefficient of the self‐thermophoresis motion is linearly dependent on chemical reaction rate, as described by a stochastic model. Abstract : Self‐propulsion of a Janus plasmonic nanomotor is presented that is driven by a chemical reaction. The mechanism of self‐phoretic motion is explained as self‐thermophoresis, and a stochastic model was developed to describe the relation between the diffusion coefficients of self‐thermophoresis motion with chemical reaction rate.